The Influence of Supply-Chain Resilience on Competitive Advantage and Firm Performance - Hosfaikoni Hadi, Nizar; Herianingrum, Sri (International Journal of Supply Chain Management, 2020)
The prime goal of the present literature is to examine the role of risk management culture along with re-engineering, collaboration and supply chain management on the firm performance along with the competitive advantage of the Islamic banks in Indonesia. The data has been used for analysis are collected through questionnaires from the employee of Islamic banks that are connected to the supply chain process while smart-PLS has been used to analyze this data. The results revealed that all the predictors such as risk management culture, re-engineering, collaboration and supply chain management have a positive association with firm performance along with the competitive advantage of the Islamic banks in Indonesia. These findings are suitable for the policymakers who want to develop policies for banking sector related to supply chain and firm performance along with the new research who want to investigate this topic in future.